1999
DOI: 10.1109/75.808038
|View full text |Cite
|
Sign up to set email alerts
|

A 530-GHz balanced mixer

Abstract: We report on the design and performance of a 530-GHz balanced SIS mixer, the first balanced mixer in this frequency range. This quasi-optical balanced mixer utilizes a cross-slot antenna on a hyperhemispherical substrate lens with eight superconductor-insulator-superconductor (SIS) junctions and a 180 lumped element IF hybrid circuit. The local oscillator (LO) and the radio frequency (RF) signal, orthogonal in polarization to each other, are coupled to the mixer using a wiregrid polarizer. The noise performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 7 publications
(7 reference statements)
0
9
0
Order By: Relevance
“…[2]), and the other is the 180 • hybrid type balanced mixer (eg. [3]). The quadrature hybrid type balanced mixer contains a quadrature hybrid as an RF-hybrid, while on the other hand the 180 • hybrid type balanced mixer includes a 180 • hybrid as an RF-hybrid.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[2]), and the other is the 180 • hybrid type balanced mixer (eg. [3]). The quadrature hybrid type balanced mixer contains a quadrature hybrid as an RF-hybrid, while on the other hand the 180 • hybrid type balanced mixer includes a 180 • hybrid as an RF-hybrid.…”
Section: Introductionmentioning
confidence: 93%
“…So far, several balanced mixers have been reported at submillimeter-wave bands, such as a 200-300 GHz coplanar waveguide type [2], and a 530 GHz quasioptical type [3,4]. These balanced mixers were integrated to contain all of the components in a block.…”
Section: Introductionmentioning
confidence: 99%
“…Wider IF bandwidths are possible through the use of a more sophisticated 180 hybrid design, perhaps integrated on-chip. It is also possible to use this device as a balanced mixer [14].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent experimental and theoretical work [197]- [207] has shown that a 90% coupling efficiency may be achieved using optimized antennas and lenses. Dual-polarization designs are also possible [103], [208], [209]. Planar antenna calculations are typically carried out using rigorous moment-method techiques, and the effect of the lens is evaluated using ray-tracing and diffraction calculations, sometimes including multiple internal reflections.…”
Section: Design Approachesmentioning
confidence: 99%
“…Development goals include wide RF bandwidth with fixed-tuned operation, wide IF bandwidth, dual polarization, balanced mixers, sideband separation, and beam-lead contacts [19], [192]- [194], [208], [209], [241]- [251]. The ALMA memo series [252] is a particularly valuable source of technical information for this area, describing the latest progress being made by the numerous institutions involved in ALMA development.…”
Section: F New Directionsmentioning
confidence: 99%